Defining Color Change in Pitaya: A Close Look at Betacyanin Synthesis Genes in Stenocereus queretaroensis - Morales, Javier; Araujo-Sanchez, Jorge; Castro-Concha, Lizbeth; Ku, Angela; Pereira-Santana, Alejandro; Miranda-Ham, María de Lourdes; Castaño, Enrique (Frontiers in Sustainable Food Systems, 2021)
Betalains are tyrosine-derived plant pigments present in several species of the Caryophyllales order. Betalains are classified in red betacyanins and yellow betaxanthins and are implicated in plant stress tolerance and visual attraction for pollinators. The compounds are used as natural colorants in many industries. Today, there is little information on betalain biosynthesis with several key enzymes that remain unknown on plants of the Caryophyllales order. Omic tools have proven to be very useful in gaining insights into various molecular mechanisms. In this study, we used suspensions cells from fruits of the cactus S. queretaroensis. Two growing conditions were used to perform RNA-seq and differential expression analysis to help identify betalain biosynthesis-related genes. We found 98 differential expressed genes related to aromatic amino acids and betalain biosynthesis pathways. Interestingly, we found that only one gene of the betalain synthesis pathway was differentially expressed. The rest of the genes belong to the aromatic amino acid pathway, including hydroxy phenylpyruvate related genes, suggesting the possibility of an alternative biosynthetic pathway similar to that observed in legumes.